Autobiography writing instruction: The journey of a teacher participating in a systemic functional linguistics genre pedagogy professional development. (April 2021) - Brisk, María Estela; Tian, Zhongfeng; Ballard, Ed
Abstract: Teaching writing has evolved from a focus on product to an emphasis on process. More recently, interest in genre pedagogy informed by systemic functional linguistics (SFL) has emerged. This article reports on a narrative analysis of a 3rd grade teacher's development of writing instruction. This teacher participated for 10 years in a school-university collaboration at a U.S. urban elementary school with a multilingual population. SFL genre pedagogy, instruction that draws content from SFL theory and instructional practices from the teaching and learning cycle (TLC) (Rose & Martin, 2012; Shi & Chen, 2020), successfully scaffolded writing instruction for bilingual students of different levels of English proficiency. Participation in a long term, whole school, collaborative professional development, with full principal support, allowed this teacher to evolve in the way he taught autobiography writing over the span of four years. Classroom observations revealed the steady transformation of instruction and the changes in the writing of four cohorts of bilingual students. This study adds to the extant research on the impact of SFL genre pedagogy on writing development and illustrates the value of professional development that is long term and gives agency to teachers to adapt SFL genre pedagogy to their students' needs.